Depression during pregnancy - Magdalena Wójcik; Grzegorz Boreński; Przemysław Szabat; Julita Poleszak; Marta Szabat; Joanna Milanowska (Kazimierz Wielki University, 2019)
Introduction: Depression during pregnancy seems to be dominated by the postpartum depression. It is important to remember about this condition and its symptoms as they are easy to be mistaken with mood changes and other behavioural changes common during pregnancy. Although we know the risk factors for this condition, we still do not know its complex etiology. Moreover, there is also not enough information about the treatment. The aim of the study: The purpose of this systemic review was to collect and analyse causes and possibilities of treatment depression during pregnancy. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: depression, treatment, pregnancy. Description of the state of knowledge: Currently the most common treatment for pregnant women suffering from depression are selective serotonin reuptake inhibitors, especially citalopram, escitalopram, paroxetine, fluoxetine, fluvoxamine and sertraline. However, their potential side effects affecting the fetus is a controversial issue. The results of many studies are not consistent. Summary: It is still not known how to treat depression during pregnancy properly. Psychotherapy, considered as a basic way of treatment, is always recommended. However, the usage of selective serotonin reuptake inhibitors is still open to debate.